PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENYUSUNAN DAN PENETAPAN PERATURAN DESA DI DESA BENDUNG AIR TIMUR KECAMATAN KAYU ARO - Eflinur, Eflinur; Syofiarti, Syofiarti (UNES Journal of Swara Justisia, 2017)
This study examines the role of Village Consultative Body (BPD) in preparing and establishing Village Rules. Article 1 of Law Number 6 Year 2014 explains that the village is a community unit adjacent to the authority to regulate and manage government affairs, the interests of community based initiatives, appropriate origins, and/or customary rights recognized and respected within the government system of the Republic of Indonesia. The publication of Law Number 6 Year 2014 on the Village brings the ideals of village renewal. The Village Consultative Body is an institution that performs a governmental function whose members represent the representatives of village communities based on their regional representations and are democratically established. The Village Consultative Body as an element of village government organization established as a democracy village forum has one important function based on Article 55 of Law Number 6 Year 2014 on Village, which is first, proposing/initiating, discussing and agreeing on the draft of village regulations with the Village Head. Second, to dig, collect, collect, formulate and channel the aspirations of the village community; Third as a partner of the village government, ie consult and coordinate each other in terms of making village regulations. This study uses secondary data as the main data collected through literature study and primary data collected based on interview results.